1997
DOI: 10.1128/mcb.17.3.1144
|View full text |Cite
|
Sign up to set email alerts
|

The Decline in Human Alu Retroposition Was Accompanied by an Asymmetric Decrease in SRP9/14 Binding to Dimeric Alu RNA and Increased Expression of Small Cytoplasmic Alu RNA

Abstract: Alu interspersed elements are inserted into the genome by a retroposition process that occurs via dimeric Alu RNA and causes genetic disorders in humans. Alu RNA is labile and can be diverted to a stable left monomer transcript known as small cytoplasmic Alu (scAlu) RNA by RNA 3 processing, although the relationship between Alu RNA stability, scAlu RNA production, and retroposition has been unknown. In vivo, Alu and scAlu transcripts interact with the Alu RNA-binding subunit of signal recognition particle (SRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 48 publications
2
32
0
Order By: Relevance
“…Previous studies have shown that random mutations in the right monomer can have a modest effect on the RNA level of Alu elements , that deletion of the right half decreases Alu activity by an order of magnitude (Dewannieux et al 2003), and that deviation from Alu subfamily consensus sequences, particularly those >10% divergence, affects Alu retrotransposition efficiency (Bennett et al 2008). In addition, previous studies altering the SRP9/14 binding motif in SINE RNAs showed a profound influence on activity (Sarrowa et al 1997;Dewannieux et al 2003;Bennett et al 2008). Some of the influence might include the specific bases that define the subfamilies themselves.…”
Section: (Students Paired T-test) (C)mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that random mutations in the right monomer can have a modest effect on the RNA level of Alu elements , that deletion of the right half decreases Alu activity by an order of magnitude (Dewannieux et al 2003), and that deviation from Alu subfamily consensus sequences, particularly those >10% divergence, affects Alu retrotransposition efficiency (Bennett et al 2008). In addition, previous studies altering the SRP9/14 binding motif in SINE RNAs showed a profound influence on activity (Sarrowa et al 1997;Dewannieux et al 2003;Bennett et al 2008). Some of the influence might include the specific bases that define the subfamilies themselves.…”
Section: (Students Paired T-test) (C)mentioning
confidence: 99%
“…In addition, the older subfamily members have accumulated random mutations affecting the RNA secondary structures and/or the interactions with other components necessary for amplification (Sinnett et al 1991;Alemán et al 2000). For instance, mutations near the 59 end of the Alu sequence have been found to alter binding ability to SRP9/14 causing inactivation of the Alu activity (Sarrowa et al 1997;Bennett et al 2008). In an effort to define Alu activity, Bennett and colleagues looked at the 280-bp ''core'' sequence of an Alu element (the left and right monomers) and determined that mutations within the primary sequence play a role in Alu activity levels, but that many of the old Alu subfamily members would be expected to remain active (Bennett et al 2008).…”
mentioning
confidence: 99%
“…One can propose that these changes correspond to the fine-tuning of SINEs to the critical factors of their amplification. For instance, the changes in Alu sequence modulating the Alu RNA capacity to bind the SRP9/14 complex gave rise to subfamilies with different amplification rate (Sarrowa et al, 1997). LINE RT is another factor of SINE amplification.…”
Section: Emergence Of Sine Subfamiliesmentioning
confidence: 99%
“…Many of these exonized Alu elements are part of alternatively spliced transcripts (Sorek et al 2002). Left Alu monomers can be expressed as stable small cytoplasmic (scAlu) RNA and right monomers are thought to be less stable than left monomers (Chang et al 1996;Sarrowa et al 1997;Li and Schmid 2004).…”
Section: Introductionmentioning
confidence: 99%